Validation of Sea Surface Temperature From GK-2A Geostationary Satellite and Error Reduction Considering Impact of Satellite Zenith Angle - Kyung-Ae Park; Hye-Jin Woo; Stephane Saux Picart; Anne O'Carroll; Eunha Sohn; HuiTae Joo; Joon-Soo Lee; Joon-Yong Yang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
This study evaluates the accuracy of sea surface temperature (SST) data produced by Korea's second geostationary satellite, GK-2A, over its first four years of operation (2019–2023). The root mean square difference (RMSD) and bias between satellite-derived SSTs and in situ measurements were approximately 0.5 and −0.04 K, respectively, satisfying the target accuracy. Errors exhibited latitude-dependent variations and differed between day and night observations. SST was found to be overestimated in conditions of weak wind (<3 m s−1) and underestimated during nighttime. Additionally, SST estimates were higher in conditions of high atmospheric humidity and lower during dry conditions. In regions with developed oceanic fronts, the intensity of the fronts linearly increased the RMSD of the satellite SST. A notable increase in SST uncertainty was observed when the satellite zenith angle (SZA) exceeded 50°. To address this, eight additional SST estimation formulas considering both linear and nonlinear relationships related to the SZA were developed and validated. The newly derived formula reduced the influence of the SZA, especially at high SZAs. The study emphasizes the critical role of the SZA in contributing to SST errors and highlights the need for continuous verification and improvement of SST accuracy before its utilization. By proposing optimal algorithms for SST retrievals from geostationary satellites, this study is anticipated to improve the monitoring of SSTs in regions covered by GK-2A. Given the high frequency of observations from geostationary satellites, findings highlight the necessity of optimizing zenith angle corrections in geostationary satellite SST operations for reliable global SST applications.